Cigarette consumption and biomarkers of nicotine exposure during pregnancy and postpartum. (23rd July 2018) - Taghavi, Taraneh; Arger, Christopher A.; Heil, Sarah H.; Higgins, Stephen T.; Tyndale, Rachel F.
Abstract: Background and Aims: Smokers can regulate their nicotine intake by altering the number of cigarettes smoked per day (CPD) and their smoking intensity. The current study aimed to compare the utility of self‐reported CPD, total nicotine equivalents (TNE) and urinary cotinine to estimate nicotine intake during pregnancy. Design: Longitudinal smoking behavior and biomarker data were collected at early pregnancy, late pregnancy and at postpartum as part of a smoking cessation trial to examine voucher‐based incentives for decreasing smoking. Setting: Obstetric practices in Burlington, Vermont, United States. Participants: A subset of participants ( n  = 47) from the parent trial, recruited between December 2006 and June 2012, who provided a urine sample at each assessment during early pregnancy, late pregnancy and postpartum. Measurements: Smoking was assessed using self‐reported CPD, TNE, TNE/CPD and urinary cotinine. Findings: Pregnant smokers reported smoking 10.4 CPD at early pregnancy, 7.2 CPD at late pregnancy (a 31% reduction at late pregnancy, P  = 0.001) and 8.6 CPD at postpartum (a 19% increase from late pregnancy, P  = 0.08). TNE exposure was 41% ( P  = 0.07) and 48% ( P  = 0.03) lower at early and late pregnancy, respectively, compared to postpartum. TNE/CPD was on average 167% higher at late pregnancy compared to early pregnancy ( P  = 0.01) and remained high at postpartum, where it was 111% higher compared to early pregnancy ( P  = 0.007). Uriniary cotinine underestimated nicotine intake by 55% during early pregnancy and by 65% during late pregnancy compared to postpartum ( P interaction  < 0.001); the underestimation was greater in slower ( P interaction  < 0.001) versus faster ( P interaction  = 0.04) nicotine metabolizers. Conclusions: Neither cigarettes smoked per day (CPD) nor cotinine provides an accurate estimate of nicotine exposure during pregnancy. CPD underestimates nicotine intake substantially due to under‐reporting and/or higher intensity of smoking, while cotinine underestimates nicotine intake markedly due to accelerated nicotine (and cotinine) metabolism during pregnancy.